2018
DOI: 10.2147/cmar.s176515
|View full text |Cite
|
Sign up to set email alerts
|

Significance of circulating tumor cells in osteosarcoma patients treated by neoadjuvant chemotherapy and surgery

Abstract: PurposeBy examining and identifying circulating tumor cell (CTC) counts and subtypes of peripheral blood in osteosarcoma patients, we evaluated the relationship between CTCs and characteristics of osteosarcoma patients, as well as CTC changes after neoadjuvant chemotherapy and surgery.MethodsCanPatrol™ CTC technology was used to detect CTCs in peripheral blood before and after treatment in 32 osteosarcoma patients. Peripheral blood samples from 10 healthy volunteers were included as controls and examined for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
2
23
1
Order By: Relevance
“…Limited studies of OSA CTC in humans also report a higher number than typically noted for carcinomas, but not nearly as high as those in our study (30,31,44). OSA is a highly aggressive neoplasm in dogs, and circulating OSA cells may at times be observed even on routine blood smear review (data not shown); therefore, frequent CTCs may be a biological feature of the tumor.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Limited studies of OSA CTC in humans also report a higher number than typically noted for carcinomas, but not nearly as high as those in our study (30,31,44). OSA is a highly aggressive neoplasm in dogs, and circulating OSA cells may at times be observed even on routine blood smear review (data not shown); therefore, frequent CTCs may be a biological feature of the tumor.…”
Section: Discussioncontrasting
confidence: 52%
“…OSA is a highly aggressive neoplasm in dogs, and circulating OSA cells may at times be observed even on routine blood smear review (data not shown); therefore, frequent CTCs may be a biological feature of the tumor. Limited studies of OSA CTC in humans also report a higher number than typically noted for carcinomas, but not nearly as high as those in our study (30,31,44). Strengths of our study are that blood samples from dogs were analyzed multiple times, including immediately before death, which provided a dynamic picture of CTC frequency.…”
Section: Discussionmentioning
confidence: 42%
“…However, only CTCs expressing epithelial cell adhesion molecule (EpCAM) will be identified with the CellSearch system . Compared with the CellSearch platform, which uses anti‐EpCAM‐coated magnetic beads to capture CTCs, one study found that patients with an increased percentage of mesenchymal CTCs (M‐CTCs) after treatment had a worse prognosis based on CanPatrol technology . The CanPatrol technique could identify CTCs expressing both epithelial‐ and mesenchymal type‐related antigens.…”
Section: Discussionmentioning
confidence: 99%
“…39,43 Compared with the CellSearch platform, which uses anti-EpCAM-coated magnetic beads to capture CTCs, one study found that patients with an increased percentage of mesenchymal CTCs (M-CTCs) after treatment had a worse prognosis based on CanPatrol technology. 44 The CanPatrol technique could identify CTCs expressing both epithelialand mesenchymal type-related antigens. Moreover, as a result of 99.98% of leukocytes being depleted and a low number of leukocytes remaining on the membrane, it is easier to observe CTCs under a microscope with the CanPatrol technique.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma (OS) is a common cancer of the musculoskeletal system in teens and is a leading cause of cancer death and disability worldwide [1]. The most involved sites are the distal femur, the proximal humerus, the proximal tibia, and the metaphysis [2]. The age of peak incidence rate ranges from 14 to 26 years old, especially 14 to 19 years old, and this constitutes a separate specific subgroup who suffer osteosarcoma [3].…”
Section: Introductionmentioning
confidence: 99%